Comparing Fears in South African Children with and without Visual Impairments. (May 2013) - Visagie, Lisa; Loxton, Helene; Ollendick, Thomas H.; Steel, Henry
Introduction: The aim of the study presented here was to determine whether significant differences exist between the fear profiles of South African children in middle childhood (aged 8–13) with different levels of visual impairments and those of their sighted counterparts. Methods: A differential research design was used, and a total of 129 assenting children from three schools in the Western Cape province of South Africa participated. This convenience sample included 67 children with various degrees of visual impairments (20 with severe impairments and 47 with moderate impairments), and 62 gender- and age-matched sighted children in the control group. All the children were administered a short demographic questionnaire and the South African Fear Survey Schedule for Children (FSSC-SA). Results: The results of the FSSC-SA indicated that the most feared item for the children with visual impairments was "Fire– getting burned" and that of the sighted children was "getting HIV." The 10 most common fears of both groups were related mainly to situations in which the possibility of danger and harm was present, with the majority of fears loading onto Factor I (fear of danger and death) of the FSSC-SA. Consistent with previous research, gender differences were apparent across the number, level, and pattern of fears, with the girls consistently reporting more fears than the boys. In addition, the severely visually impaired group reported more fears, a greater intensity of fears, and a more complex pattern of fears than their moderately visually impaired and sighted counterparts. Discussion: These results are discussed in terms of possible influencing factors. Implications for practitioners: The results of the study provide teachers, parents, and others who are involved in the day-to-day lives of children with visual impairments with a glimpse into the children's emotional worlds. They also provide a foundation upon which future intervention and treatment strategies may be built.